Determinan Surplus (Defisit) Underwriting Dana Tabarru’ Pada Perusahaan Asuransi Umum Syariah Indonesia - Didi; Djaddang, Syahril; Mulyadi, JMV (Metris: Jurnal Sains dan Teknologi, 2024)
This study aims to examine the effect of claims, reinsurance and investment returns on the tabarru' underwriting surplus (deficit) which is moderated by the proportion of tabbaru' funds. The approach used in this research is a quantitative approach. The sample used in this research is companies in the Islamic financial institution industry, especially general Islamic insurance companies that are registered with the Financial Services Authority (OJK) as of December 31, 2021, totaling 18 companies. Research data were analyzed using panel regression analysis techniques with the Eviews program 12.0. The results of this study indicate that claims have a significant effect on the underwriting surplus (deficit) of tabarru' funds, likewise the proportion of tabbaru' funds can moderate the effect of claims on the underwriting surplus (deficit) of tabarru' funds. The results of this study also prove that reinsurance and investment returns are not a factor that can partially affect the underwriting surplus (deficit) of tabarru' funds, but simultaneously, claims, reinsurance and investment returns and the moderating effect of the proportion of tabarru' funds can affect the surplus (deficit) underwriting tabarru' funds with a contribution of 17.19%.